Factors influencing cure by transsphenoidal selective adenomectomy in paediatric Cushing's disease. - Storr, H; Afshar, F; Matson, M; Sabin, I; Davies, K; Evanson, J; Plowman, P; Besser, G; Monson, J; Grossman, AB; Savage, M (2005)
OBJECTIVE: Early diagnosis and effective treatment of paediatric Cushing's disease (CD) is necessary to minimise associated morbidity. Accepted first-line treatment is selective transsphenoidal microadenomectomy (TSS), which can be technically difficult, and cure rates vary considerably between centres. In our paediatric CD patient group we have assessed the possible factors which may influence cure by TSS. SUBJECTS AND METHODS: From 1983-2004, 27 paediatric patients (16 males, 11 females; mean age+/-s.d., 13.1+/-3.2 yr; range, 6.4-17.8 yr) with CD were managed in our centre and underwent TSS. Sixteen patients (59%), seven males and nine females (mean age+/-s.d., 14.2+/-2.5 yr; range, 8.2-17.8 yr), were cured (post-operative serum cortisol < 50 nM). Eleven patients, nine males and two females (mean age+/-s.d., 11.5+/-3.6 yr; range, 6.4-17.8 yr) had post-operative cortisol levels above 50 nM (2-20 days), with mean serum cortisol levels at 09:00 h of 537 nM (range 269-900 nM) indicating a lack of cure. These 11 patients received external beam pituitary radiotherapy (RT). One patient with a pituitary macroadenoma had a post-operative cortisol level of < 50 nM but 0.8 yr later showed an elevated cortisol and residual disease. RESULTS: The patients cured by TSS alone were significantly older than those not cured (P = 0.038; Student's t test). All patients had CT/MRI pituitary imaging: 14 were reported to have microadenomas and one macroadenoma, while 12 were reported as normal. Bilateral simultaneous inferior petrosal sinus sampling (BSIPSS) with i.v. corticotropin-releasing hormone (CRH) administration was introduced as a pre-operative investigation in 1986 and was performed in 21 patients (78%), on BSIPSS, 16 (76%) had evidence suggesting pituitary adrenocorticotropic hormone (ACTH) secretion (central to peripheral (IPS:P) ACTH ratio after CRH of > or = 3.0) and 16 (76%) showed lateralisation of ACTH secretion (IPSG of > or = 1.4). There was concordance between the BSIPSS finding and the position of the microadenoma at surgery in 17/21 (81%) patients. Of the 16 patients showing lateralisation of ACTH secretion, 12 (75%) were cured by TSS. Of the four without lateralisation of ACTH, suggesting a midline lesion, 3 (75%) were cured by TSS. Post-operative pituitary hormone deficiencies in the patients cured by TSS were: pan-hypopituitarism 1/16, isolated growth hormone deficiency (GHD) (peak GH on glucagon/ITT < 1-17.9 mU/l) 9/16 and diabetes insipidus 3/16. CONCLUSION: Over a 21-year period selective adenomectomy by TSS cured 59% of all paediatric CD patients, with higher age favouring cure. Introduction of BSIPSS resulted in the demonstration of a high rate of lateralisation of ACTH secretion consistent with the surgical identification of the adenoma, and therefore appears likely to have contributed to the higher surgical cure rate.